Pola makan, rasio lingkar pinggang pinggul (RLPP) dan tekanan darah di Puskesmas Mergangsan Yogyakarta - Putu Diah Ernitasari; Bambang Djarwoto; Tri Siswati (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2009)
Background: Dietary pattern has changed in almost all over the world that nowadays people consume high fat and low fiber diet. These changes are responsible for the increased obesity problems in community. Ratio between waist circumference and hip circumference could become an indicator for android obesity. This type of obesity has a stronger relationship with increasing risk factor of coronary heart disease, hypertension, and diabetes mellitus, compared to gynecoid type obesity.Objective: To identify relationship between dietary pattern and waist hip circumference ratio with blood pressure at Mergangsan Primary Health Care Yogyakarta.Method: This was an observational research with cross sectional study, held at November 2008. Research population was all adult patients came to Mergangsan Primary Health Care. Independent variable including dietary pattern and hip waist circumference ratio (RLPP), and blood pressure as dependent variable. Characteristic sample data were collected using questionnaire and interview, data of waist–hip circumference ratio were collected using metlin (accuracy 0.1 cm), data of blood pressure were measured with sphygmomanometer, and data of dietary patterns were collected using semi-quantitative food frequency questionnaire (FFQS). Samples were taken with judgmental technique sampling. Data were analyzed using chi-square and odds ratio.Results: Percentage samples that consumed carbohydrate source diet frequently was 91.1%, whereas samples that consumed animal and plant diet served were 71 % and 88.9%; vegetables and fruits 65.6% and 52.5%, 78.9% samples seldom consumed milk, 92.2% frequently consumed oil and others consumed frequently 90%. Female samples with obesity nutritional status were 55.6%. Mean value of waist hip circumference ratio were 1.03 ± 0.13 and 0.88 ± 0.1 for male and female, respectively. Dietary pattern of some foods and blood pressure showed significant relationship, that were vegetables (p = 0.003; OR = 0.194), fruits (p = 0.00, OR = 1.17), milk (p = 0.010; OR 5.76), and others (p = 0.047; OR 5.76). Waist hip circumference ratio also had significant relationship with blood pressure (p = 0.009).Conclusion: There were significant relationships between dietary pattern of vegetables, fruits, milk, and others with blood pressure. Waist hip circumference ratio also had significant relationship with blood pressure.